Broth Microdilution and Gradient Diffusion Strips vs. Reference Agar Dilution Method: First Evaluation for Clostridiales Species Antimicrobial Susceptibility Testing - Florian Baquer; Asma Ali Sawan; Michel Auzou; Antoine Grillon; Benoît Jaulhac; Olivier Join-Lambert; Pierre H. Boyer (MDPI AG, 2021)
Antimicrobial susceptibility testing of anaerobes is challenging. Because MIC determination is recommended by both CLSI and EUCAST, commercial broth microdilution and diffusion strip tests have been developed. The reliability of broth microdilution methods has not been assessed yet using the agar dilution reference method. In this work, we evaluated two broth microdilution kits (MICRONAUT-S Anaerobes® MIC and Sensititre Anaerobe MIC®) and one gradient diffusion strip method (Liofilchem®) for antimicrobial susceptibility testing of 47 Clostridiales isolates (Clostridium, Clostridioides and Hungatella species) using the agar dilution method as a reference. The evaluation focused on comparing six antimicrobial molecules available in both microdilution kits. Analytical performances were evaluated according to the Food and Drug Administration (FDA) recommendations. Essential agreements (EA) and categorical agreements (CA) varied greatly according to the molecule and the evaluated method. Vancomycin had values of essential and categorical agreements above 90% for the three methods. The CA fulfilled the FDA criteria for three major molecules in the treatment of Gram-positive anaerobic infections (metronidazole, piperacillin/tazobactam and vancomycin). The highest rate of error was observed for clindamycin. Multicenter studies are needed to further validate these results.